Linguistic Sexism in the Iranian EFL Junior High School Textbooks - Vahdatinejad, Shapour; Hamid, Bahiyah Abdul (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2017)
Gender biased textbook can internalize the sexist concept and can affect the students’ mindset and behavior against the other gender. As in Iran, school textbooks are the only resource for majority of both teachers and students, unbiased textbooks are necessary for students to build up their role in addressing the other gender in their lives and society. To examine this issue, this study attempted to explore the status of linguistic sexism in the current Iranian EFL school textbooks (three volumes) published by the Iranian Ministry of Education in 2008. A systematic quantitative content analysis was carried out to investigate whether both genders have been addressed equally or not. Results revealed that linguistic sexism is obvious and the textbooks can be considered sexist because the males outnumber females and are mostly the focal characters. The textbooks present students, in their early exposure to the English language, with an unfair, unbalanced and inexcusable representation of women. The roles of females and their realistic contributions to the society are not well represented in the textbooks. Some implications are advised for teachers, textbook writers and policy makers.